AuBr3-catalyzed chemoselective annulation of isocyanates with 2H-azirine - Wu, Yufeng; Tian, Bing; Witzel, Sina; Jin, Hongming; Tian, Xianhai; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Chemistry - a European journal, 2019)
The chemoselective cyclization of isocyanates with 2H-azirine was achieved with AuBr3 as catalyst. This transfer sets the stage for the synthesis of aromatic oxazole-ureas in a tandem process. The addition of a catalytic amount of phosphite enhances the process enormously. The reaction can also be performed in a one-pot process using benzoyl azide instead of isocyanate under the same conditions. A detailed study on the role of the phosphite that was applied as an additive revealed that only non-coordinated phosphite can reduce gold(III) and that gold(I) coordinated phosphite is not oxidized. Accompanied by the reduction of gold, HBr is generated in situ, which turned out to be the actual promotor in combination with the remaining AuBr3. The positive effect of acid can be explained by a strong N-Au coordination, which tends to break more easily in the presence of small amount of protic acid in the reaction solution.
Im Titel ist "3" hinter AuBr tiefgestellt
Version of record online: December 14, 2018
Gesehen am 16.07.2019